THE EFFECT OF STUDENTS' READING INTEREST ON LEARNING OUTCOMES IN INDONESIAN LANGUAGE LESSON CLASS III AT SDN 1 PANUNGGUL - Zakkiyyatul Aula; Widia Nur Jannah; Prabawati Nurhabibah (Journal of Education and Teaching Learning, 2026)
This research is motivated by the low learning outcomes of students in Indonesian subjects which are influenced by low interest in reading. The results of the preliminary study show that students' interest in reading is still low, which has an impact on their learning outcomes. This study aims to determine the influence of reading interest on the learning outcomes of grade III students in Indonesian language subjects at SDN 1 Panunggul. The research uses a quantitative approach with the Pre-Experimental Design method in the form of One Group Pretest-Posttest Design. The research subjects amounted to 34 students who were selected using saturated sampling techniques. Data was collected through learning outcome tests, reading interest questionnaires, and documentation, then analyzed using descriptive statistics, Shapiro-Wilk normality test, Wilcoxon Signed Rank Test, and N-Gain test. The results showed that the average reading interest increased from 73.94 to 85.41, while the average learning outcome increased from 66.47 to 82.79. The results of the Wilcoxon test obtained an Asymp value. Sig. (2-tailed) of 0.000 (<0.05), which indicates a significant influence of reading interest on student learning outcomes. The average N-Gain value of 0.4662 is in the medium category, so learning using narrative text materials is considered quite effective in improving Indonesian learning outcomes. Thus, the increase in reading interest contributes positively to improving student learning outcomes.